Mysticism in Lalon and Tagore: A question of textual Influence and Intertextuality - Ahmed, Jarif Faiyaz (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2019.